Activation of ENaC by AVP contributes to the urinary concentrating mechanism and dilution of plasma - Mironova, Elena (Am J Physiol Renal Physiol, 2014)
Arginine vasopressin (AVP) activates the epithelial Na(+) channel (ENaC). The physiological significance of this activation is unknown. The present study tested if activation of ENaC contributes to AVP-sensitive urinary concentration. Consumption of a 3% NaCl solution induced hypernatremia and plasma hypertonicity in mice. Plasma AVP concentration and urine osmolality increased in hypernatremic mice in an attempt to compensate for increases in plasma tonicity. ENaC activity was elevated in mice that consumed 3% NaCl solution compared with mice that consumed a diet enriched in Na(+) with ad libitum tap water; the latter diet does not cause hypernatremia. To determine whether the increase in ENaC activity in mice that consumed 3% NaCl solution served to compensate for hypernatremia, mice were treated with the ENaC inhibitor benzamil. Coadministration of benzamil with 3% NaCl solution decreased urinary osmolality and increased urine flow so that urinary Na(+) excretion increased with no effect on urinary Na(+) concentration. This decrease in urinary concentration further increased plasma Na(+) concentration, osmolality, and AVP concentration in these already hypernatremic mice. Benzamil similarly compromised urinary concentration in water-deprived mice and in mice treated with desmopressin. These results demonstrate that stimulation of ENaC by AVP plays a critical role in water homeostasis by facilitating urinary concentration, which can compensate for hypernatremia or exacerbate hyponatremia. The present findings are consistent with ENaC in addition to serving as a final effector of the renin-angiotensin-aldosterone system and blood pressure homeostasis, also playing a key role in water homeostasis by regulating urine concentration and dilution of plasma.